2020
DOI: 10.3390/md18080395
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Three Polysaccharides on the Oxidative Stress Induced by Acrylamide in a Saccharomyces cerevisiae Model

Abstract: Saccharomyces cerevisiae was used as a model to explore the preventive effect of two marine polysaccharides separately derived from Sepia esculenta ink (SIP) and Laminaria japonica (FL) as well as one terrestrial polysaccharides from Eleocharis tuberosa peel (WCPP) on toxic injury induced by acrylamide (AA). The growth of yeast was evaluated by kinetics indexes including doubling time, lag phase and maximum proliferation density. Meanwhile, intracellular redox state was determined by contents of MDA and GSH, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…It is therefore essential to replenish antioxidants for the purpose of guarding against illnesses and aging. The antioxidant potentials of extracts, phenolics and polysaccharides from E. dulcis corm pulp and peel have been confirmed by different in vitro models 13,70,82,83 . For instance, ethanol extract of E. dulcis corm pulp shows stronger scavenging capacities against superoxide anions, 1,1‐diphenyl‐2‐picrylhydrazyl (DPPH) and hydroxyl radicals than vitamin C (VC) and butylated hydroxytoluene (BHT), two well‐known commercial antioxidants.…”
Section: Health Benefitsmentioning
confidence: 88%
See 3 more Smart Citations
“…It is therefore essential to replenish antioxidants for the purpose of guarding against illnesses and aging. The antioxidant potentials of extracts, phenolics and polysaccharides from E. dulcis corm pulp and peel have been confirmed by different in vitro models 13,70,82,83 . For instance, ethanol extract of E. dulcis corm pulp shows stronger scavenging capacities against superoxide anions, 1,1‐diphenyl‐2‐picrylhydrazyl (DPPH) and hydroxyl radicals than vitamin C (VC) and butylated hydroxytoluene (BHT), two well‐known commercial antioxidants.…”
Section: Health Benefitsmentioning
confidence: 88%
“…For other extracts, such as water extract, non-starch polysaccharides could also contribute to antioxidation. 19,83 On the other hand, Ren et al found that aureusidin (compound 53), a flavonoid that had been isolated from E. dulcis corm peel, elicits antiinflammatory activity in lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages via the reactive oxygen species (ROS)dependent mitogen-activated protein kinase (MAPK) pathway, and unveiled that heme oxygenase-1 (HO-1), a key antioxidase that can protect cells from oxidative stress-induced damage, is involved in the anti-inflammatory process of aureusidin. 69,86,90 However, the above-mentioned activities of tested samples measured by in vitro assays would not accurately reflect the real status in vivo.…”
Section: Wileyonlinelibrarycom/jsfamentioning
confidence: 99%
See 2 more Smart Citations
“…MDA production is formed after the breakdown of lipid hydroperoxides and is a biomarker of free radical injury in pathologies associated with free radical and oxidative stress. The levels of MDA as a marker of the oxidative stress response are considered as a sign of cell injury and promote the oxidant/antioxidant imbalance in cells [31,32]. hs-CRP as an inflammatory marker promotes acute and chronic inflammatory responses and is related to an adverse prognosis.…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%